Comparison of the acoustic behavour between paper waste of HVS and carton in similar composite - Abdul Ghofir, Hidjan; ., Sutanto (International Journal of Engineering and Technology, 2018)
One of the hazardous environmental pollution that harms human health is Noise. Porous and vibrous materials are considered can be used for reducing noise. The purpose of the investigation is synthesizing and characterizing two kinds of acoustical composites based on Activated Zeolite with Carton and Activated Zeolite with HVS Paper Waste as building material components for noise reduction. Synthesizing each composite was conducted by chemical and mechanical mixing, and characterizing process was carried out by using EDS, FTIR, SEM and Impedance Tube. The absorption coefficient was measured in the frequency range between 125 Hz up to 6000 Hz. The results show that both have significant values for absorbing noise at the audible frequency range between 1200 Hz to 2200 Hz.